Implementasi IoT Menggunakan Google Spreadsheets Pada Sistem Monitoring Temperatur Dan Kelembaban Ruangan - Elfirza Rosiana; Abdurahman; Irawati; Ravi Joentera (CV. Multi Kreasi Media, 2024)
Every place has the potential for danger, even a closed room. Temperature, air circulation, humidity are some of the factors that can cause health and comfort problems if not well regulated. So it is necessary to make a system that can monitor the temperature and humidity of the room to stay in comfort and safety. In this research, a device has been made that can monitor temperature and humidity using a DHT11 sensor. The measured data is sent via the Internet of Things (IoT) to facilitate analysis and decision making without having to come to the physical device. The test results of this tool have a relative error in temperature measurements of 1.14%, 1.51% and 0.76%. Data transmission is successfully done and displayed on the blynk application with an average delay of 2.3 seconds. While sending data shown via google spreadsheets application has an average delay of 3.3 seconds.